ANALYZING ISLAMOPHOBIA AS HATE SPEECH: AL-ATTAS' VIEWS ON THE CORRUPTION OF KNOWLEDGE - Hamid Fahmy Zarkasyi; Jarman Arroisi; Muhammad Taqiyuddin; Mohammad Syam'un Salim (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2019)
The phenomenon of Islamophobia has always been a contemporary issue, especially in a world that is supposed to be global and full of diversity. In fact, in some Muslim-majority countries, the phenomenon is actually spread. Further study found that among the reasons was a misunderstanding in exploring and understanding Islam as a religion. Especially on the meaning of Islam as a universal religion for humans. Methodologically, this literature research model uses a historical literacy approach in the form of a Western phobia of Islam (especially religion) in the Middle Ages (anti-semitic), primary sources of Islamic teachings, and Islamic religious philosophy specifically excavated from Syed Muhammad Naquib al-Attas. Al-Attas’ analysis is used based on his capacity to understand ideas about metaphysics and Western civilization and Islam itself. The theoretical study is focusing on al-Attas' conception of 'corruption of the knowledge' that occurs as a result of 'loss of adab'. This is a global challenge for contemporary Muslims, the 'pursuit of knowledge' ; that is, the spread of 'erroneous science' that is like true, but contains falsehood and brings damage to the correct understanding of Islam. This study found that 'the corruption of the Knowledge' about Islam often results in Islamophobia; which begun with misunderstanding about the very essential things in Islam. Muslims join in phobias towards their religion because of the loss of adab. Most of the misconceptions result from 1) studying Islam without referring to scientific authority 2) framing social media about Islam 3) Secularization which reduces Islam is only limited to ancient Arabic culture.